New record of Boa constrictor occidentalis Philippi, 1873 (Serpentes: Boidae) in San Juan province, Argentina - Martínez, Tomás Agustín (2015)
We document the first record of Boa constrictor in Valle Fértil department, San Juan province, Argentina. The specimen was collected and deposited in the herpetological collection of the Department of Biology, Universidad Nacional San Juan. This record extends the known distribution for this species in San Juan province by 105 km.